The effect of social media use on eating behaviors and physical activity among university students. - Güneş, Musa; Demirer, Büşra (Journal of Public Health: From Theory to Practice (2198-1833), 2025)
Aim: This cross-sectional study aimed to evaluate the relationship between the duration of social media use time, eating disorders, and physical activity level in university students. Subjects and methods: A total of 562 university students between the ages of 18–29 were included in the study. Study data were collected through an online survey system, including the survey form, some sociodemographic information, social media use information, Eating Attitude Test-26 (EAT-26) scale, and International Physical Activity Questionnaire-Short Form. The data were analyzed with the SPSS 27.0 statistical package program. Results: The mean duration of social media use of individuals (mean age 21.18 (2.04) years) participating in the study was 4.76 (3.34) hours/day. The participants' mean EAT-26 scale scores were 18.20 (13.73), and 37.5% of the individuals were at risk of eating disorders according to the cut-off score. At the same time, the physical activity levels of the individuals were low at 44.8%, moderate at 35.8%, and high at 19.4%. A very weak positive correlation was found between the duration of social media use and sedentariness (r = 0.174; p < 0.001). Conclusion: The study data shows that as the duration of social media use increases, the sedentary behaviors of individuals increase, and using social media accounts with visual content is associated with the risk of eating disorders. Considering these results, it is thought that to prevent unconscious social media use, education/seminars should be given to different age groups, including appropriate body image, healthy nutrition, and physical activity recommendations.